Experimental Study on Shear Strengthening of RC Deep Beams with Large Openings Using CFRP - Chin, Siew Choo; Fadzil, Mat Yahaya; Doh, Shu Ing; Kusbiantoro, Andri; Wen, Khai Chong (2015)
This research deals with the experimental study on the behaviour of reinforced concrete (RC) deep beams with large circular openings and openings strengthened using externally bonded Carbon Fiber Reinforced Polymer (CFRP) composites in shear. The structural behavior including the load deflection behaviour, crack pattern, failure mode as well as strengthening configuration was investigated. A total of three (3) specimens of beams with design strength of 35 MPa were tested to failure under 4-points loading. The beam specimens included a solid RC deep beam as a control beam and two RC deep beams with large circular openings to determine the behaviour of un-strengthened and strengthened beams using CFRP wrap. The beams had a cross section of 120 mm x 600 mm and a length of 2400mm. The openings were placed at the support on both sides of the shear span, at a distance 300 mm from the edge of the beam. The circular opening was designed to a standard of 0.45h which is considered as large circular opening with a diameter of 270 mm. Shear span-to-depth ratio (a/h) was 0.83 in which the distance between the loading point and the support was 500 mm. One of the test parameters presented in this paper was surface strengthening method. RC deep beam with the presence of large circular openings in the shear zone experienced substantial strength loss with a reduction of 51% as compared to the original structural capacity of the control beam. Comparing with the control beam,surface strengthening method could only manage to re-gain the beam capacity up to 56%.